Antipsychotic effects of sex hormones and atypical hemispheric asymmetries. (June 2020) - Hodgetts, Sophie; Hausmann, Markus
Abstract: Functional cerebral asymmetries (FCAs) are a fundamental principle of brain organisation. While specific patterns of asymmetry are characteristic of healthy human brains, atypical or reduced FCAs have been reported for several psychotic disorders, including schizophrenia and mood disorders. However, it is unclear whether atypical FCAs reflect a predisposition to psychotic disorders or a compensatory neural strategy for the progressive structural and functional changes in the brain associated with psychosis. A separate stream of research has demonstrated the antipsychotic effects of sex hormones in clinical populations. Moreover, modern neuroscience has shown that sex hormones, particularly estrogen and progesterone, can affect FCAs due to their organising effects (e.g., during prenatal development), and also by their activating effects throughout life (e.g., in younger women during the menstrual cycle or in post-menopausal women as a consequence of hormone therapy). By combining these research streams, this narrative literature review explores the relationship between the neuromodulatory properties of estrogen, FCAs and psychotic and psychotic-like symptoms. This research is not only of theoretical interest for the understanding of FCAs and psychotic symptoms, but might also be of clinical relevance for the development of stratified treatment approaches for women and men suffering from psychosis and mood disorders.